The Promise of Disease Management in Greece - Konstantinos Stamatiou; Richard Lacroix; Eleni Almpani; Konstantinos Katsanos; Georgios Tzitzikos; Maria Saridi (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Background: Disease Management (DM) is an approach to health care that coordinates resources across the entire health care delivery system and throughout the course of a disease. Objectives: The purpose of the present study was to evaluate the DM implementation in a country like Greece, with distinct geographical characteristics and non-symmetrical distribution of health care services.  Methods: Recent bibliographic data about DM were gathered from electronic databases emphasizing on the Greek status and the Greek Health Care System (GHCS).  Results: The present article discusses the current role, the future contribution and the expected results of DM in Greece. DM still is not well applied in Greece. This is due to the economical, geographical and organisational particularities of the country. There is a big gap between the GHCS and the requirements of the Institute Of Medicine. The percentage of Greek population receiving screening services is low. Posttreatment guidelines for patients are also limited. Numerous initiatives have taken place for the creation of national disease registries but remain incomplete. Despite the increased prevalence of some diseases, few seek health care services, which can be primarily attributed to erroneous beliefs, so the need for education and prevention programs is increasing.  Conclusion: We will be able to count for a high level health care system in Greece when the philosophy of DM changes and modifications is applied properly, especially when patient education and behavioral commitment will evolve as the major contributors to the successful treatment.